2009
DOI: 10.4314/ajfand.v9i8.48405
|View full text |Cite
|
Sign up to set email alerts
|

Influence of potato cultivar and stage of maturity on oil content of French fries (chips) made from eight Kenyan potato cultivars

Abstract: French fries (chips) are increasingly becoming indispensable in menus of many restaurants and hotels in major Kenyan towns due to their relatively lower consumer prices compared to other foods. When foods are deep-oil-fried, the amount of oil absorbed by the food is important since nutritionally, the amount of oil absorbed has a marked bearing on the number of calories supplied by the food. Fried foods such as chips may contain a considerable amount of oil to such extent that their consumption is of concern to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
10
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 9 publications
3
10
0
1
Order By: Relevance
“…The differences among the genotypes may be due to their differences in genetic makeup for flavour and a growing environmental factor. This result was supported by Pardoet al, (2000) and Abong et al, (2009), who investigated and reported that values obtained for each of the varietal sensory characteristics of flavor, significantly differed among cultivars due to their genetic make-ups.…”
supporting
confidence: 54%
“…The differences among the genotypes may be due to their differences in genetic makeup for flavour and a growing environmental factor. This result was supported by Pardoet al, (2000) and Abong et al, (2009), who investigated and reported that values obtained for each of the varietal sensory characteristics of flavor, significantly differed among cultivars due to their genetic make-ups.…”
supporting
confidence: 54%
“…Texture Parameter (Hardness). The textural properties of fried starch based products are influenced by gelatinization of starch, sugar content, and the strength of the cell wall [13]. In this study, the parameter of texture measured is hardness and is indicated by the breaking force (N).…”
Section: Resultsmentioning
confidence: 99%
“…Loss of moisture was directly related to oil uptake. The lower oil uptake in french fries and chips made from tubers stored at 11 • C could be due to their high dry matter content resulting from moisture loss caused by evaporation and respiration (Abong et al, 2009;Santerre et al, 1986). …”
Section: Tuber Dry Matter and Oil Uptake Of French Fries And Chipsmentioning
confidence: 99%
“…Dry matter content is an important determinant of yield, and high dry matter content is positively correlated with mealiness, crispness, and higher yield (Ramezani and Aminlari, 2004) and negatively correlated with oil uptake by chips (Santerre et al, 1986) and french fries (Abong et al, 2009).…”
mentioning
confidence: 98%